A case report of IgG4-related hepatic inflammatory pseudotumor in a 3-year old boy - Wan, Qian; Xu, Zhongjin; Liu, Xiaohui; Wu, Zhuqiang; Zhong, Qingmei; Wu, Chongjun (Frontiers in Immunology, 2024)
Background: Hepatic Inflammatory Pseudotumor (IPT) is an infrequent condition often masquerading as a malignant tumor, resulting in misdiagnosis and unnecessary surgical resection. The emerging concept of IgG4-related diseases (IgG4-RD) has gained widespread recognition, encompassing entities like IgG4-related hepatic IPT. Clinically and radiologically, corticosteroids and immunosuppressive therapies have proven effective in managing this condition. Case Presentation: A 3-year-old Chinese boy presented to the clinic with an 11-month history of anemia, fever of unknown origin, and a tender hepatic mass. Blood examinations revealed chronic anemia (Hb: 6.4 g/L, MCV: 68.6 fl, MCH: 19.5 pg, reticulocytes: 1.7%) accompanied by an inflammatory reaction and an elevated serum IgG4 level (1542.2 mg/L). Abdominal contrast-enhanced computed tomography unveiled a 7.6 cm low-density mass in the right lateral lobe, while magnetic resonance imaging demonstrated slight hypointensity on T1-weighted images and slight hyperintensity on T2-weighted images, prompting suspicion of hepatic malignancy. A subsequent liver biopsy revealed a mass characterized by fibrous stroma and dense lymphoplasmacytic infiltration. Immunohistochemical analysis confirmed the presence of IgG4-positive plasma cells, leading to the diagnosis of IgG4-related hepatic IPT. Swift resolution occurred upon initiation of corticosteroid and mycophenolate mofetil therapies.This study underscores the diagnostic approach to hepatic IPT, utilizing histopathology, immunostaining, imaging, serology, organ involvement, and therapeutic response. Early histological examination plays a pivotal role in clinical guidance, averting misdiagnosis as a liver tumor and unnecessary surgical interventions.